"Have you heard about X?": (Mis)management of mortality in academia. Issue 7 (9th August 2022) - Małecka, Katarzyna A.
Abstract: An overview of the literature shows that various types of employee death in academia are relatively unexplored. In part a dialogic response to a study reflecting upon the impact of an academic's suicide, this multiple case study focuses on organizational and personal reactions to the deaths of four coworkers at four Polish universities. To present the experiences of the participants in a holistic manner, this study is phenomenological in design, incorporating semi-structured interviews followed by thematic data explicitation. Eight thematic areas were explored yielding results that diverge from most guidelines on the constructive management of loss in the workplace.